Sustainable rangeland management toolkit for resilient pastoral systems - Louhaichi, Mounir; Davies, Jon; Gamoun, Mouldi; Hassan, Sawsan; Abu-Zanat, Mahfouz; Neffati, Mohamed; Tadros, Maher; Ouled Belgacem, Azaiez; Rajabov, Toshpulat; Annouri, Laila; Al Rahahleh, Laith; Baqain, Razan; et al. (International Center for Agricultural Research in the Dry Areas, 2023)
INNOVATION PROFILE of Sustainable rangeland management toolkit with a holistic and multidisciplinary approach for addressing the biophysical and sociocultural aspects under changing climate and land use leading towards more resilient pastoral systems.